Ambiente laboral en los departamentos del área administrativa de la dirección provincial del Consejo de la Judicatura de Los Ríos - Castro Cerezo, Maryorie Isamara (2020)
This research work occurs due to the different problems that arise in the administrative areas of the Provincial Directorate of the Los Ríos Judicial Council, given that there is favoritism or, on the other hand, that they are not being taken into account as a staff. useful of the company. That is why the current investigative work has the main objective of obtaining information about the work environment in the departments of the administrative area, and thus carry out a study of how this can affect job performance, taking into account that public employees can go through Adverse circumstances that can directly influence your job performance or your attitude towards work. Having finished studying the data on the issues raised, we found that employees in certain periods of work do not feel comfortable in their workplace, either due to lack of communication, lack of motivation, friction between employees, behavior, attitudes. negatives, stress from professional burnout and others, it should be emphasized that the lack of commitment on the part of the workers is what is causing delays in the processes or poor coordination in planned activities